Study the Toll-like Receptor 2 and Dectin-1 in mice treated with beta‐ glucans and infected with Salmonella Typhimurium - Mahdi, Nidhal R. (University of Thi-Qar Journal of Science, 2013)
Objective: Toll-like receptors (TLRs) are essential components for the induction of innate immune responses in different tissues including the small intestine, spleen and mesenteric lymph nodes. We investigated the expression of TLR2 in these tissues in mice infected with Salmonella Typhimurium. In this study we have examined how dectin-1, a lectin family receptor for β-glucans, collaborates with TLR-2 in recognition of microbes.Methods :In this study two groups of mice were treated with the β- glucan (local and commercial extract) and infected with(1x10 6 CFU/ml) S. Typhimurium at different intervals group 1 at day zero and group 2 after seven days of the experiment .The immunohistochemistory assay has been performed to detect TLR-2 and dectine-1 in the tissues of small intestine, spleen and mesenteric lymph nodes of the mice; the principle ofthis assay was done according to the manufacturer instructions (U.S.biological) .Results: In the immunohistochemistory assay, positive cells were indicated by cytoplasmic staining and the percentage of positive in 100 cells was recorded and graded. The grades were 1+ (<25%), 2+ (25-75%) and 3+ (>75%). Statistical analysis with Chi- Square tests revealed that there were significant differences (p˂0.05) between groups, also between grades within the same group in the small intestine, spleen with TLR2 expression; also we demonstrated the same results with Dectin-1 expression in the small intestine and mesenteric lymph nodes, except in the spleen which showed that there were no any relevant differences (p˂ 0.05 ) between the groups and the cell- grades.